KAJIAN TOTAL BIOMASSA DAN SIMPANAN KARBON RERUMPUTAN SERTA SIFAT FISIKA KIMIA TANAH PADA LAHAN RERUMPUTAN DENGAN KELAS LERENG BERBEDA DI DAERAH TANGKAPAN AIR DANAU TOBA Studi Kasus Kecamatan Silahisabungan Kabupaten Dairi - Edy Frans Redoman Nadapdap; Abdul Rauf; Asmarlaili Sahar Hanafiah (Universitas Sumatera Utara, 2013)
ABSTRACT“Study of Biomass total and The Grass Carbon Reserves and Charateristhic of soil Chemistry incatchment area of Lake Toba: case study at kecamatan Silahisabungan Kabupaten Dairi”. To knowthe biomass production total and carbon reserves and charateristhic of physical chemistry of soil.This study have been done an December 2011 to March 2013. Samples of soil,biomass, and litterwas taken from three types of slopes, they are quite ramps, wavy and a bit steep. The method ofbiomass measurement is “Destructive sampling method” by cutting over all plants part on the landwith the windth is 2m x 2m. Then separated each part , crots, leaves and trunk and pondered the dryweight. The result of this study showed that the biomass production total on grass land is greaterthan on forest land bur charateristhic of physical chemistry of forest lans was better than the grassland.Keyword : biomass, grass, slope, Toba lake water catchment area